Diagnosis and management of chronic pancreatitis. Issue 958 (5th August 2005) - Gupta, V; Toskes, P P
Abstract : Chronic pancreatitis represents a condition that is challenging for clinicians secondary to the difficulty in making an accurate diagnosis and the less than satisfactory means of managing chronic pain. This review emphasises the various manifestations that patients with chronic pancreatitis may have and describes recent advances in medical and surgical therapy. It is probable that many patients with chronic abdominal pain are suffering from chronic pancreatitis that is not appreciated. As the pathophysiology of this disorder is better understood it is probable that the treatment will be more successful.